EXAMINING REPUTATION AND SERVICE INNOVATION ON THE PERFORMANCE OF ISLAMIC RURAL FINANCING BANK - Iwa Karniwa (Sosiohumaniora, 2023)
Sharia BPRS have an important role in supporting the economy in Indonesia through financing for the small and medium sectors. West Java is the province with the largest number of BPRS (27) besides Central Java (27), with the highest working capital, investment, and consumption values compared to other provinces. This study aims to examine the effect of bank reputation and service innovation on the performance of BPRS in West Java. This study used a quantitative approach using a cross-sectional survey design. The questionnaire was designed using a 5-point Likert Scale. Samples were taken from as many as 50 respondents. The data is then processed using the Partial Least Square (PLS) method with SmartPLS 3.0 software. The results of the hypothesis testing show that only service innovation has proven to have a significant effect on the performance of BPRS in West Java, while bank reputation has no significant effect. The results of this study have implications for BPRS management banks to pay more attention to the development of service innovations aimed at creating products with special characteristics that are different from conventional BPRs, coupled with a wide variety of products that can be chosen by customers with superior benefits. Excellence in service delivery is also an important factor in making customers satisfied with BPRS services. Better utilization of information and communication technology is needed in providing services so that customers can interact more quickly and easily with the bank.